Edukasi Penggunaan Obat Alternatif Berbasis Tanaman Obat yang Aman untuk Masyarakat di Dusun Plurugan, Kelurahan Tirtonirmolo, Kecamatan Kasihan, Kabupaten Bantul, Daerah Istimewa Yogyakarta - Dwi Asih Ramadhani; Rima Erviana; Rifki Febriansah; Muhamad Zaenul Asror; Cyntia Putri Happy Paradita; Nova Chalistya; Muhammad Thesa Ghozali (Institut Agama Islam Sunan Giri Ponorogo, 2025)
Gout is a metabolic disorder with a high prevalence in society and has the potential to reduce individuals’ quality of life, particularly due to joint pain and limited mobility. Health education plays a strategic role in increasing public knowledge regarding risk factors, symptoms, prevention efforts, and management strategies for gout. This activity aimed to improve the understanding of residents in Dusun Plurugan through interactive health education based on medicinal plants. The method included lectures, interactive discussions, and the distribution of educational materials in the form of leaflets. Evaluation was carried out using pre-tests and post-tests to assess the effectiveness of the program. The results showed a significant increase in participants’ understanding after the education sessions. It is hoped that this activity will encourage the community to adopt a healthier lifestyle and perform early detection of gout symptoms to prevent further complications.